Bag of Tricks: A Set of Techniques and other Resources to Help 14C Laboratory Setup, Sample Processing, and Beyond. Issue 3 (26th July 2016) - Santos, Guaciara M; Xu, Xiaomei
Abstract: Over the last few decades, radiocarbon laboratories have used different procedures for measuring a broad range of carbonaceous materials. To produce reliable results, the processes employed for sample processing, graphite target production, and spectrometer measurement must be rigorous, well tested, and reproducible. Most of the procedures have been developed, improved, and published as part of the laboratories' quality control and research programs, and can be frequently found in the literature. Nevertheless, there are suites of laboratory techniques (or "small useful skills"), products, and other resources that either have never been described in publications, or have been somewhat hidden in much larger scientific articles and reports. We feel that with the rapid rise of newer laboratories and facilities, a set of resourceful suggestions might come in handy. Here we gathered these skill sets that can be used in all aspects of 14 C sample processing, with the intention to simplify and expedite procedures, from glass-tube making to graphitization and measurements. We also included some miscellaneous items to help in laboratory setup.